Effect of biosecurity measures and early detection systems, mitigation measures and surveillance strategies on the spread of HPAI and LPAI between farms. Issue 1 (30th January 2017) - Mulatti, P; Dorotea, T; Vieira, JT; Bonfanti, Lebana; Marangon, S
Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2016.4687/full